Evidence of Holocene climatic change and human impact in northwestern Yunnan Province: High-resolution pollen and charcoal records from Chenghai Lake, southwestern China. (January 2018) - Xiao, Xiayun; Haberle, Simon G; Li, YanLing; Liu, Enfeng; Shen, Ji; Zhang, Enlou; Yin, Jianji; Wang, Sumin
High-resolution pollen and charcoal records from Chenghai Lake, northwestern Yunnan Province of China, are presented in this study. These records reveal changes in climate and human activity since 8220 cal. yr BP, and the drivers of climatic change are further discussed based on spectral analysis of Tsuga and evergreen oak pollen percentages. The pollen record indicated that the climate in the low altitude area was relatively warm and moderately dry, whereas the climate in the high altitude area was relatively cool and humid during the period 8220–4670 cal. yr BP, corresponding to the Holocene climate optimum, although the seasonality of precipitation increased between 5180 and 4670 cal. yr BP. From 4670 to 3470 cal. yr BP, the temperature declined, and the precipitation and its seasonality decreased. Between 3470 and 1860 cal. yr BP, the temperature was still relatively low, and precipitation appeared to decrease further. At the same time, human activity represented by agricultural planting began to influence this study area, but the intensity of human activity was relatively weak. After 1860 cal. yr BP, the climate was gradually becoming drier and the intensity of human activity such as deforestation and slash-and-burn agriculture increased. Spectral analysis of Tsuga and evergreen oak pollen percentages shows statistically significant periodicities of ~1500 and ~200 years at the ≥95% confidence level, which suggests that insolation and feedback interactions on millennial to centennial scales are the primary forcing mechanisms of the southwest monsoon and past climatic change during the Holocene in northwestern Yunnan Province, southwestern China.